Historical prevalence of infectious diseases and entrepreneurship: The role of institutions in 125 countries - Omang O. Messono; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
This study examines the effects of the historical prevalence of infectious diseases on contemporary entrepreneurship. Previous studies reveal the persistence of the effects of historical diseases on innovation, through the channel of culture. Drawing on the epidemiological origin of institutions, we propose a framework which argues that the impact of infectious disease prevalence on contemporary entrepreneurship is mediated by property rights. The central hypothesis posits that a guarantee of property rights reduces the effect of past diseases on entrepreneurship. Using data from 125 countries, we find strong and robust evidence on the proposed hypothesis and other results. Property rights are higher in countries where the prevalence of diseases was low, which leads to good entrepreneurship scores. In contrast, countries with high disease prevalence did not have time to develop strong institutions to secure property rights. This explains their low level of entrepreneurship today. These results are robust to alternative methods and measures of property rights. Furthermore, our results also confirm the level of development, culture and the digitalization of economies as transmission channels between past diseases and the current level of entrepreneurship.
Keywords: I0; J24; I21; I31; 330; entrepreneurship; institutions; diseases; property rights